PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH PROVINSI SUMATERA SELATAN - Ardiyan Natoen Evada Dewata Yuliana Sari Susi Ardiani Karina Leonasari (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This research is intended to provide partial and simultaneous information about the influence of local taxes and user charges on the income of the province of South Sumatra. This research uses secondary data of sample of budget realization report of South Sumatera Province 2001-2015. Analysis techniques in this study using multiple linear regression analysis, descriptive analysis,classical assumption test, hypotesis test such as f test and t test with SPSS software version 23.0. The results showed that the local tax partially significant effect on the local revenue of the South Sumatra Province. In regional retribution variable indicate that retribution does not have a significant effect to the original income of South Sumatra Province. Meanwhile, the results of research simultaneously or together show that the variable of local taxes and local levies have a significant effect on the original income of the province of South Sumatra.